Nanostructural analysis of finogel (Fish Nano Gelatin) for new process development - Monsur, Hammed Ademola; Jaswir, Irwandi; Salleh, Hamzah Mohd. (2010)
One of the most important applications of nanotechnology is process evaluation and development. DiHerent pattern was observed felr gelatins pretreated diHerently. Four types of pre~ treatment solution were used during fish gelatin extraction in 2010 International Conference on Process Engineering & Advanced Materials 62 this study. Thev were acetic acid (A), acetic acid~~aCI (AS), acetic acid~NaOH (AB) and acetic acid~NaOH~NaCl (ABS). Results showed that each pretreatment gave diHerent nano imaging patterns; A (fibril), AS (zig~zag cracks), AB (straight rods) and ABS (cross~linked rods). Cross~linked rods observed in ABS denote adequate removal ofnon~collagen content of the fish skin and increase its surface area. ABS is suggested as the best pretreatment lex perch fish gelatin.